Effect of Employee Benefits on Organizational Growth of Consumer Goods Firms in Nigeria - Agubata, Nonye Stella; Okolo, Livinus Ikenna; Ogwu , Stephen Obinozie (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2022)
Employees have physical and emotional needs so the wellbeing of the workforce cannot be overlooked. This study examined the effect of employee benefits on business growth using a sample of ten consumer goods companies listed on the Nigerian Stock Exchange. The panel data used in this study is from the annual report of the individual companies from 2012-2019 and was analyzed using the Eviews. The study carried out descriptive statistics with undistorted original data; tests such as Pearson correlation and the variance inflation factor were also performed. Finally, the Pesaran CD test was used to check the cross-sectional dependence before estimating the panel regression, which corrected the cross-sectional dependence with Period SUR. The Fixed Effect regression result showed that gratuity, pension and medical allowance, which were the measures of employee benefits, had a positive significant effect on organizational growth (measured in terms of assets), The study, therefore, concludes that employee benefits in the consumer goods sector have a positive and significant effect on business growth, with the exception of the medical allowance. Therefore, the study recommends that business organizations trying to get the most out of employees for growth should initiate and improve the payment of benefits to employees and initiate and improve pension payment.